Skin-related neglected tropical diseases in Angola: a retrospective analysis - Lídia P. Almeida-Voumard; Cecília C. Almeida; Ernesto Afonso; Clarry N. Luvualu; José M. Pedro; Maiza R. Baptista; Pascoal O. Alberto; Juliano V. Isaías; Christian F. Voumard (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Objective: This was a retrospective analysis of the epidemiological and clinical profile of ten main skin neglected tropical diseases (NTDs) and appraisal of the role of dermatologists in the control and elimination of those diseases. Methods: Analysis of routine data and special investigations carried out by the Ministry of Health between 2017 and 2021, and internet search of published information on skin NTDs in Angola. Results: Except for yaws, all skin NTDs under review remain endemic. Previously unknown foci of Buruli ulcer (BU), cutaneous leishmaniasis (CL), and guinea worm disease (GWD) were detected in recent years. Leprosy, onchocerciasis, lymphatic filariasis, scabies, and snake bites are endemic countrywide. Weak laboratory services are a major constraint to confirm clinically suspected cases. The growing collaboration between public health workers, family doctors, and dermatologists is strengthening integrated approaches in NTDs control and elimination programs. Conclusions: The elimination of leprosy, BU, CL, and GWD as public health problems does not warrant the total interruption of their transmission chain over time. Effective case diagnosis and epidemiological surveillance are key strategies to control and eliminate skin NTDs. In addition to patient centered disease diagnosis and management, dermatologists must actively support field investigations, innovative training programs, and advocacy on skin NTDs.